Therapeutic Strategies in Pulmonary Hypertension - Fuso, Leonello; Baldi, Fabiana; Di Perna, Alessandra (Frontiers in Pharmacology, 2011)
Pulmonary hypertension (PH) is a life-threatening condition characterized by elevated pulmonary arterial pressure. It is clinically classified into five groups: patients in the first group are considered to have pulmonary arterial hypertension (PAH) whereas patients of the other groups have PH that is due to cardiopulmonary or other systemic diseases. The management of patients with PH has advanced rapidly over the last decade and the introduction of specific treatments especially for PAH has lead to an improved outcome. However, despite the progress in the treatment, the functional limitation and the survival of these patients remain unsatisfactory and there is no cure for PAH. Therefore the search for an “ideal” therapy still goes on. At present, two levels of treatment can be identified: primary and specific therapy. Primary therapy is directed at the underlying cause of the PH. It also includes a supportive therapy consisting in oxygen supplementation, diuretics, and anticoagulation which should be considered in all patients with PH. Specific therapy is directed at the PH itself and includes treatment with vasodilatators such as calcium channel blockers and with vasodilatator and pathogenetic drugs such as prostanoids, endothelin receptor antagonists and phosphodiesterase type-5 inhibitors. These drugs act in several pathogenetic mechanisms of the PH and are specific for PAH although they might be used also in the other groups of PH. Finally, atrial septostomy and lung transplantation are reserved for patients refractory to medical therapy. Different therapeutic approaches can be considered in the management of patients with PH. Therapy can be established on the basis of both the clinical classification and the functional class. It is also possible to adopt a goal-oriented therapy in which the timing of treatment escalation is determined by inadequate response to known prognostic indicators.